Drug-like Properties and ADME of Xanthone Derivatives: The Antechamber of Clinical Trials - Sara Gomes, Ana; Brandão, Pedro; Sofia Garcia Fernandes, Carla; Ramos Pinto Correia da Silva, Marta; Emília da Silva Pereira de Sousa, Maria; Maria de Magalhães Pinto, Madalena (Current Medicinal Chemistry, 2016)
Xanthone derivatives have been described as compounds with a privileged scaffold exhibiting diverse biological/pharmacological activities, what directed the interest to pursue the development of these derivatives into drug candidates. Nevertheless, to achieve this purpose it is crucial to study their pharmacokinetics and toxicity (PK/tox) properties as decision endpoints to continue or interrupt the development investment. This review aims to expose the most relevant analytical methods used in the physicochemical and PK/tox studies in order to detect, quantify, and identify different bioactive xanthones. Analyzing the main results from in vitro and in vivo systems towards ADME properties such as solubility, lipophilicity, pKa, chemical and metabolic stability, permeability, transporters modulation, and plasma protein binding, it is possible to uncover some threats governing the PK properties and to understand the bioavailability and drugability of xanthone derivatives. The last section of this review focuses on a case-study of the development of the drug candidate DMXAA, which has reached clinical trials, to provide the paths and the importance of PK/tox parameters of this scaffold. The data assembled in this review intends to guide for tackling issues in the design of potential lead compounds and drug candidates with a xanthone scaffold.
Keywords: physicochemical properties